HANDBALL AND ITS STRUCTURE (Fiep Bulletin - online, 2011)
The handball history has several origins, but all of them come into consensus where it is referred that "the father of handball" is Karl Schenenz, the same being a historical representative for the sport. In Brazil, the handball was brought by the German immigrants to São Paulo until being extended to the whole country. The handball game is structured and has as a target to make "Goal". It shows different characteristics from other sports, stating risks, elements and relations in the game, taking into consideration physical, psychological and social aspects worked together. In the handball game, the essential fundaments are the steps, the passes, the dribbles, the guile, the forward and the reception with it specific objectives, systems and tactics, the offensive as the defensive system. It is considered an important game into the physical educational classes, although it must be observed the pedagogical process and the proper age in its learning, which can offer innumerable possibilities of movements and improving motor abilities since childhood.
Keywords: Handball; Fundaments; Physical Education